Association of physical activity with glycaemic control and cardiovascular risk profile in 65 666 people with Type 2 diabetes from Germany and Austria. Issue 8 (18th April 2014) - Hermann, G.; Herbst, A.; Schütt, M.; Kempe, H.‐P.; Krakow, D.; Müller‐Korbsch, M.; Holl, R. W.; the Diabetes Patienten Verlaufsdokumentation (DPV)‐initiative and the BMBF Competence Network Diabetes Mellitus
Abstract Aims To provide representative data from routine diabetes care concerning the physical activity levels of people with Type 2 diabetes, and to show the association of activity level with cardio‐metabolic risk profile in a gender‐specific analysis. Methods The anonymized data from 65 666 subjects with Type 2 diabetes, who have been receiving treatment in specialized diabetes institutions, were analysed using a large multi‐centre database. The population was categorized as physically inactive (PA0), active 1–2 times per week (PA1), active >2 times per week (PA2), and then stratified by age (20–59 and 60–80 years). BMI, glycaemic control (measured by HbA1c levels), blood pressure, lipid profile and therapeutic regimen were adjusted for age, gender and diabetes duration. Results Most subjects were inactive (PA0: 90%; PA1: 6%, PA2: 4%). BMI, HbA1c and lipid profiles were better in older subjects and hypertension rates were lower in younger subjects. In both age groups, BMI, HbA1c (both P < 0.0001) and triglycerides (P < 0.002) were lower in the most active group PA2 compared with the inactive group PA0. HDL was higher in elderly (P < 0.0001) and pulse pressure (P = 0.03) lower in younger most active subjects only. Insulin therapy was used more frequently by the physically inactive and by older people. Conclusions This survey indicates that glycaemic control and cardio‐metabolic risk profiles in people with Type 2 diabetes are positively related to physical activity. The effects of physical activity were beneficial in younger as well as in older people. The high number of inactive people with diabetes underlines the need to promote physical activity and sport.